Interspinous Process Decompression Improves Quality of Life in Patients with Lumbar Spinal Stenosis. (2nd July 2018) - Nunley, Pierce D.; Patel, Vikas V.; Orndorff, Douglas G.; Lavelle, William F.; Block, Jon E.; Geisler, Fred H.
Abstract : Lumbar spinal stenosis has been shown to negatively impact health-related quality of life. Interspinous process decompression (IPD) is a minimally invasive procedure that utilizes a stand-alone spacer to serve as a joint extension blocker to relieve neural compression in patients with spinal stenosis. Using the 5-year results from an FDA randomized controlled trial of IPD, the quality of life in 189 patients treated with the Superion® spacer was evaluated with the SF-12. Physical and mental component summary (PCS, MCS) scores were computed preoperatively and at annual intervals. For the PCS, mean scores improved from 29.4 ± 8.1 preoperatively to 41.2 ± 12.4 at 2 years (40%) and to 43.8 ± 11.6 at 5 years (49%) (p<0.001 for both comparisons). At 2 years, 81% (103 of 128) of subjects demonstrated maintenance or improvement in PCS scores. The mean MCS score improved from 50.0 ± 12.7 preoperatively to 54.4 ± 10.6 and 54.7 ± 8.6 at 2 and 5 years, respectively (p>0.10 for both comparisons). These results demonstrate that the significant impairment in physical well-being found in patients with lumbar spinal stenosis can be ameliorated, in large part, by IPD treatment.